A influência da poluição difusa e do regime hidrológico peculiar do semiárido na qualidade da água de um reservatório tropical - Oliveira, José Neuciano Pinheiro de (2012)
In semiarid region of northeast Brazil, the majority of reservoirs used for public supply has suffered degradation of water quality affected by diffuse pollution from agricultural and livestock areas of the watershed and by hydrologic regime peculiar to the region, characterized by a rainy season with higher volumes stored in reservoirs and a dry season with a reduction in water level due to high evaporation and increase of eutrophication. The Dourado reservoir, located in Currais Novos city, semiarid region of Rio Grande do Norte state, is one example of a water supply reservoir that can have degradation of water quality and impracticability of their use, due to the high external input of nutrients from non-point sources of watershed during the rainy season and increasing of eutrophication due to decrease the stored volume during the dry period. This study aimed to investigate and quantify diffuse pollution and the hydrologic regime of semiarid region in order to establish standards regarding the water quality of Dourado reservoir. The study period was between the months of May 2011 to March 2012. The diffuse pollution was quantified in terms of watershed from the mass balance of phosphorus in the reservoir, as in relation to areas under different types of land use within the riparian zone of the reservoir from the assessment of soil chemical properties and losses of phosphorus in each area. The influence of hydrological regime on water quality of the reservoir was evaluated from the monthly monitoring of the morphometric, meteorological and limnological features throughout the study period. The results showed that the reservoir has received a high load of phosphorus coming from the drainage basin and presents itself as a system able to retain some of that load tributary, giving an upward trend of the eutrophication process. Diffuse pollution by nutrients from areas under different types of land use within the riparian zone of the reservoir was higher in areas under the influence of livestock, being this area considered a potential diffuse source of nutrients to the reservoir. Regarding the water regime during the rainy season the reservoir was characterized by high concentrations of nutrients and small algal biomass, while in the dry season the reduction of volume and increase of the water retention time of the reservoir, contributing to the excessive growth algal biomass, favoring an increase in eutrophication and deterioration of water quality. In synthesis the water quality of Dourado reservoir is directed by diffuse pollution coming from the drainage basin and the hydrological regime of the peculiar semiarid region, where the rainy season is characterized by high input of allochthonous compounds from the tributaries and erosion of the soil in the reservoir riparian zone, and the dry season characterized by reducing the storage volume due to high evaporation, high residence time of water and consequent degradation of water quality due to the increase of eutrophication process